DECLARATION OF RIVERS AS SUBJECTS OF LAW IN COLOMBIA: LEGAL INNOVATION FOR BIOCULTURAL PROTECTION - Vargas-Machado, Camilo Andrés (2026)
This document is the product of a jurisprudential review of the period 2023–2024, which followed a qualitative design, an interpretive paradigm, and an inductive approach, applying a documentary technique to record all the rulings issued by the Constitutional Court of Colombia regarding the protection of fundamental rights affected by environmental issues. A documentary sampling process was conducted, leading to the creation of a data registration matrix used as an instrument to categorize the documents and conduct their hermeneutic examination and analysis. This process conclusively identified six judicial decisions in which a river was declared a subject of rights in Colombia, reflecting a transformation in the legal recognition of rivers as entities bearing rights and proposing a perspective that intrinsically links environmental protection with human rights, particularly those of ethnic communities. The study also identified a legal framework based on judicial precedents, paving the way for a biocultural approach aimed at addressing both environmental deterioration and historical inequities. However, challenges remain regarding effectiveness and representation, with the primary issue being the need to establish a clear structure for legal representation.